PERBEDAAN PELAKSANAAN OOSOUJI OLEH PARA LANSIA DAN ANAK MUDA JEPANG SAAT INI - Riani, Winda; Isnaini, Zuli Laini; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to explore differences in the implementation of theoosouji tradition, or "Great Cleansing," between the older and younger generations inJapan today. Oosouji is a traditional Japanese ritual that is related to Shinto beliefs. In practice, Oosouji is a thorough cleaning of the house which is carried out at the end of every year by Japanese people. Implementation is carried out at the end of the year in December. Based on questionnaire data, there are differences in the implementation of oosouji between the younger generation and the older generation in Japan today. Older respondents tend to still follow the ritual wholeheartedly compared to younger respondents. The elderly are considered to be more enthusiastic about doing oosouji and tend to throw away unused items. On the other hand, the younger generation tends to sell items they no longer use. This difference is influenced by several factors, such as the level of belief in Shinto, busyness, and the lifestyle of living alone which is now being adopted by many young people. However, there were also respondents who stated that oosouji would still continue in the future, although its implementation might vary depending on the region and the level of people's trust in Shinto. Using a qualitative approach in the form of a questionnaire, this research collected data from elderly and young respondents in various regions in Japan. The results showed significant differences in the way oosouji was carried out, the time spent, the areas of the house cleaned, and the meaning and values attached to the tradition between the two generations.Key words: Oosouji, Japanese traditions, elderly generation, younger generation,cultural differences, Shinto beliefs